On the influence of microstructure on the room-temperature deformation behavior of a near-α titanium alloy - Sridhar G.; Sarma D.S. (My University, 2025)
The microstructural features and mechanical properties of a near-α titanium alloy, IMI 829, subjected to β © 1991 The Minerals, Metals & Materials Society, and ASM International.